Rape myth acceptance, victim blame attribution and Just World Beliefs: a rapid evidence assessment - Hand, Christopher J. (2017)
Background: Rape is underreported, potentially because individuals self-blame and/or are blamed by others. Research predominantly illustrates male-perpetrated stranger-rape of females; thus, there may be a perception that rape myth acceptance (RMA) and victim-blaming are most prevalent in males. The purpose of this rapid evidence assessment was to investigate the availability of high-quality research into the effects of Just World Beliefs, perpetrator/victim gender, and stranger- and acquaintance/marital-rape scenarios on victim-blaming and RMA. Methods: Several electronic databases were searched for empirical papers using terms including: ‘victim blame’, ‘rape myth acceptance’, ‘Just World Beliefs’, ‘type of rape’ and ‘gender’. Gough's (2007) weight of evidence framework was used to assess quality prior to inclusion. Findings: Studies retained after filtering and quality assessment suggested that RMA was predictive of victim-blaming with both male and female ‘victims’. Rape myth acceptance is more prevalent in males even in male ‘victim’ scenarios, and Just World Belief was positively associated with RMA. Greater victim-blaming was attributed in stranger- vs. acquaintance-rape scenarios. Discussion: There are no absolute conclusions regarding the role of gender or situational factors and rape-supportive/victim-blaming attitudes. Further empirical research is required to understand the prevalence of RMA in perceptions of marital rape and, particularly, homosexual marital rape